PENGARUH MARKET SENSING CAPABILITY, BRAND IMAGE, DAN KNOWLEDGE SHARING YANG DIMEDIASI OLEH INNOVATION TERHADAP MARKETING PERFORMANCE - Nofriyan, Rofi’i; Yusuf, Akhmad Syahroni; Indrasta, Gilang Wahyu; Damayanti, Nur (ITB AAS Indonesia Surakarta, 2024)
This research investigates the factors influencing the performance and sales of insurance products at PT TASPEN (Persero) and its subsidiary, Taspen Life. The research findings highlight several key aspects. First, the market sensing capability, or the company's ability to understand the market, has a significant impact on marketing performance. Second, marketing insurance products faces challenges, such as declining premium revenue and low achievement of marketing Key Performance Indicators (KPIs). Third, innovation in marketing is key to attracting more customers and competing in an increasingly competitive market. Companies need to consider more innovative marketing strategies and unique products. Lastly, the research reveals the complexity of the relationships among the variables under study. Therefore, companies can conduct specialized marketing campaigns to improve brand image, provide knowledge sharing about marketing, consider innovation in marketing strategies, and continue research to better understand the factors influencing marketing performance. For future research, it is essential to consider elements such as risk management, pricing strategies, and external factors affecting the life insurance market. Integrating these suggestions into future research is expected to provide deeper and more valuable insights for developing more effective marketing strategies across various branches of PT TASPEN (Persero).